2013
DOI: 10.3329/icpj.v2i11.16534
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effects of different fractions of crude aqueous extract of Ficus exasperata leaves on blood pressure

Abstract: Ficus exasperata has been extensively used in folk medicine for the treatment of many ailments. The aqueous extract of leaves of this herb reduced blood pressure through its cholinomimetic effect. In this study, different fractions of the crude extract of F. exasperata leaves (FEFIX) were evaluated on blood pressure. Fractionated extracts were obtained by successive use of different solvents on the total crude extract. Phytochemical analysis was performed for each fraction and increasing doses (0.25 to 40 mg /… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Amonkan [2] showed that aqueous extract of ficus exasperata (Moraceae) leaves a dose-dependent increase in diuresis.…”
Section: Discussionmentioning
confidence: 99%
“…Amonkan [2] showed that aqueous extract of ficus exasperata (Moraceae) leaves a dose-dependent increase in diuresis.…”
Section: Discussionmentioning
confidence: 99%